1978
DOI: 10.1210/jcem-47-6-1230
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among Prostate Stroma, Plasma Estrogen Levels, and Urinary Estrogen Excretion in Patients with Benign Prostatic Hypertrophy

Abstract: Plasma testosterone, plasma estradiol, and the total estrogen excretion in the urine were obtained from patients with benign prostatic hypertrophy and correlated to the histological pattern of the resected or enucleated prostates. There was a highly significant increase of prostate stroma in association with higher individual estradiol concentrations and urinary estrogen excretion, while no apparent correlation could be found with testosterone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
2
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 21 publications
2
23
2
1
Order By: Relevance
“…Perturbation of the androgen: estrogen ratio is associated with altered growth, behavior, and pathogenesis in the prostate, particularly when the ratio of androgens:estrogens is reduced on aging. In older men, peripheral androgen levels are reduced while estrogen levels remain unchanged or become elevated, 48 -50 and increasing circulating and intraprostatic estrogen:androgen ratios have been linked to prostate disease, including benign prostatic hyperplasia [51][52][53][54][55][56] . This study demonstrates the seminal importance of maintaining the appropriate balance between androgens and estrogens during neonatal life.…”
Section: Discussionmentioning
confidence: 99%
“…Perturbation of the androgen: estrogen ratio is associated with altered growth, behavior, and pathogenesis in the prostate, particularly when the ratio of androgens:estrogens is reduced on aging. In older men, peripheral androgen levels are reduced while estrogen levels remain unchanged or become elevated, 48 -50 and increasing circulating and intraprostatic estrogen:androgen ratios have been linked to prostate disease, including benign prostatic hyperplasia [51][52][53][54][55][56] . This study demonstrates the seminal importance of maintaining the appropriate balance between androgens and estrogens during neonatal life.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence for estradiol production in the rat, canine and human prostate was demonstrated using the estrogen formation assay and/ or H 2 O release assay (6). Seppelt demonstrated a signiĀ®cant correlation between the individual physiological estradiol levels and the amount of prostate stroma (7). Suzuki et al reported that the serum E 2 /T ratio was correlated with the prostatic volume (8) and Shibata et al demonstrated that the E 2 /dihydrotestosterone (DHT) ratio in the transitional zone of human BPH was positively correlated with the prostatic volume, the proportion of stroma (%) and age (9).…”
Section: Introductionmentioning
confidence: 99%
“…The released estrogens cause increased stimulation of the prostatic stroma, resulting in excessive proliferation of the prostate and occurrence of BPH (Krieg et al, 1995;Shibata et al, 2000). Indeed, it has been suggested that estrogen is a major risk factor of BPH (Seppelt, 1978;Van Coppenolle et al, 2001). Although the mechanism by which estrogen leads to the development of BPH has not been fully understood, available studies have shown that estrogen has direct and indirect effects at the cellular level on the prostate.…”
Section: Discussionmentioning
confidence: 99%